2021
DOI: 10.1097/fjc.0000000000001048
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations With Stable Warfarin Dose Requirements in Han Chinese Patients

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…CYP2C9*2 (rs799853) and CYP2C9*3 (rs1057910) have been studied widely for their role in determining the efficacy of losartan among various populations [25,26], while rs2860905 has been commonly studied to determine the warfarin dose. Studies conducted on Caribbean Hispanic population and Han Chinese patients of valvular disease showed that rs2860905 variant is associated with warfarin sensitivity which could help in a more stable dosing of warfarin [27,28]. A recent study from Taiwan also concluded that CYP2C9 rs2860905 GG genotype increases the risk of ischemic stroke in the adult population suffering from atrial fibrillation [29].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C9*2 (rs799853) and CYP2C9*3 (rs1057910) have been studied widely for their role in determining the efficacy of losartan among various populations [25,26], while rs2860905 has been commonly studied to determine the warfarin dose. Studies conducted on Caribbean Hispanic population and Han Chinese patients of valvular disease showed that rs2860905 variant is associated with warfarin sensitivity which could help in a more stable dosing of warfarin [27,28]. A recent study from Taiwan also concluded that CYP2C9 rs2860905 GG genotype increases the risk of ischemic stroke in the adult population suffering from atrial fibrillation [29].…”
Section: Discussionmentioning
confidence: 99%